2010
DOI: 10.1016/j.brainres.2010.09.107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual segmental trisomies of human chromosome 21 syntenic regions on hippocampal long-term potentiation and cognitive behaviors in mice

Abstract: As the genomic basis for Down syndrome (DS), human trisomy 21 is the most common genetic cause of intellectual disability in children and young people. The genomic regions on human chromosome 21 (Hsa21) are syntenic to three regions in the mouse genome, located on mouse chromosome 10 (Mmu10), Mmu16 and Mmu17. Recently, we have developed three new mouse models using chromosome engineering carrying the genotypes of Dp(10)1Yey/+, Dp(16)1Yey/+, or Dp(17)1Yey/+, which harbor a duplication spanning the entire Hsa21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
141
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(156 citation statements)
references
References 59 publications
14
141
1
Order By: Relevance
“…After Pennington's seminal paper (Pennington et al 2003 )we have seen arguments on the role of the hippocampus in cognitive dysfunction in patients with TRS21 (Menghini et al 2011 ) as well as in mouse models (Smith et al 1997 ;Yu et al 2010b ). Our findings confirm the hypothesis but cast a different light on conclusions drawn.…”
Section: The Hippocampus Hypothesissupporting
confidence: 59%
“…After Pennington's seminal paper (Pennington et al 2003 )we have seen arguments on the role of the hippocampus in cognitive dysfunction in patients with TRS21 (Menghini et al 2011 ) as well as in mouse models (Smith et al 1997 ;Yu et al 2010b ). Our findings confirm the hypothesis but cast a different light on conclusions drawn.…”
Section: The Hippocampus Hypothesissupporting
confidence: 59%
“…Analyses with mouse models and partial trisomies in humans have shown that certain trisomic regions correlate with both the incidence and the severity of DS phenotypes (Richtsmeier et al 2002;Olson et al 2004bOlson et al , 2007Korbel et al 2009;Lyle et al 2009;Reynolds et al 2010;Yu et al 2010). Studies investigating the penetrance and variability in DS phenotypes have previously singled out nontrisomic genes as important factors in DS phenotypes (Epstein 2001;Kerstann et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MEF were obtained from C57BL6 wild‐type and DP16 (Yu et al, 2010) mice, as described (Xu, 2005). MEF and HEK293 cells were cultured in DMEM (Gibco, Life technologies) supplemented with 10% FBS (Natocord), 1% Glutamax and nonessential amino acids (Gibco, Life technologies), in a 5% CO2 and 37°C atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…Life span extension in mCAT mice was associated with reduced cardiac pathology, decreased DNA oxidative damage, protection against age‐related insulin resistance, and improved proteostasis, underscoring the role of cumulative oxidative damage in aging associated pathologies (Lee et al, 2010; Mao et al, 2012; Treuting et al, 2008; Umanskaya et al, 2014). To further understand the role of Nrf2 stabilization in homeostasis and survival of trisomic cells, we assessed the Nrf2 signaling pathway as well as the effect of mCAT in DS human fibroblasts (HF), and mouse embryonic fibroblasts (MEF) derived from Dp16 mice, a segmentally trisomic model that reproduces several clinical phenotypes present in people with DS, including cognitive impairment (Belichenko et al, 2015; Li et al, 2007; Yu et al, 2010). We found that chronic canonical Nrf2 activation is required to prevent extensive oxidative damage and is critical for survival of both DS HF and Dp16 MEF.…”
Section: Introductionmentioning
confidence: 99%